Comparing gender transformation in Disney adaptation: resexualization in animated and live-action Peter Pan, Alice, and Pleakley - Gusna, Aisyah Auliya; Zafira, Aurelia Afrin; Yuniar, Vira Astri (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This study examined how gender representation changed in Disney’s live-action adaptations of Peter Pan, Alice in Wonderland, and Lilo & Stitch, focusing on the shifts that appeared when animated characters are reinterpreted for contemporary audiences. The research question addressed two questions: the resexualization types and gender transformations in animated versus live-action adaptations. The study used a qualitative description design by comparing both versions of each movie. The analysis examined visual redesign, character behavior and dialogue context to identify changes in gender expression and gender characterization. This method was used to observe how each adaptation reshaped the psychological and symbolic dimension of the characters. Finding indicated two resexualization types: RT1 Gender Alteration and RT2 De-objectification. In Peter Pan, the live-action adaptation reshaped Peter from a dominant, cheeky, and impulsive boy to a more introspective and emotionally expressive character, reflected in his behavior, dialogue, and visual expressions. This RT1: Gender Alteration also signaled stronger anima side, seen in his empathy and emotional awareness. In Alice in Wonderland, Alice evolved from a passive, dependent girl to an active, confident leader, reflecting RT1: Gender Alteration and greater animus expression. Her appearance was updated to a mature style, demonstrating RT2: De-objectification. In Lilo & Stitch, Pleakley’s character shifted from feminine to neutral men’s clothing, reflecting RT2: De-objectification and increased animus side, making his characterization more balanced. The study concluded that these adaptations reshaped not only visuals but also the internal logic of character identity. Disney’s reinterpretation responded to modern cultural expectations by emotional literacy and gender expression. This shift showed characters redesign across media forms can reshape gender identity for new generation viewers.